2021
DOI: 10.1177/08901171211020997
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Experiences and Social Distancing: Insights From the Theory of Planned Behavior

Abstract: Purpose: The objective of this study is to identify the relationship between COVID-19 experiences, perceived COVID-19 behavioral control, social norms and attitudes, and future intention to follow social distancing guidelines. Design: This is a cross-sectional study. Setting: Participants responded to an on-line survey in June 2020. Subjects: The study included 3,183 residents within Quebec, Canada aged 18 and over. Measures: Measures include perceived COVID-19 related discrimination, fear of COVID-19 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 44 publications
5
29
0
1
Order By: Relevance
“…23, p< 0.05, “avoiding public spaces”, R= 0.52, p<0.001 and “canceled or postponed meetings with friends” R = 0.49, p<0.001. These results corroborate the earlier findings (Bruine de Bruin & Bennett, 2020; Frounfelker et al,2021; Shilo, Peleg & Nudelman, 2021; Vacondio et al, 2021). However, there were no significant correlations with this worry variable and D incr or T decr .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…23, p< 0.05, “avoiding public spaces”, R= 0.52, p<0.001 and “canceled or postponed meetings with friends” R = 0.49, p<0.001. These results corroborate the earlier findings (Bruine de Bruin & Bennett, 2020; Frounfelker et al,2021; Shilo, Peleg & Nudelman, 2021; Vacondio et al, 2021). However, there were no significant correlations with this worry variable and D incr or T decr .…”
Section: Resultssupporting
confidence: 93%
“…When a person indicated a greater safety distance, he or she had a stronger belief in following advice of distance and wearing a mask. As predicted from other research (Bruine de Bruin & Bennett, 2020; Frounfelker et al,2021; Shilo, Peleg & Nudelman, 2021; Vacondio et al, 2021) worry over becoming sick with Covid-19 correlated with belief in following advice , R (141) = 0.48, p <0.001.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The most common barriers to physical distancing endorsed by participants included unfavorable social norms, efficacy doubts, and distancing fatigue while injunctive social norms were the strongest independent predictor of physical distancing adherence in our hypothesis tests. Other studies have found similar connections between social norms for social distancing and distancing behaviors or intentions ( Frounfelker et al, 2021 ; Norman et al, 2020 ), with one study suggesting that norms for social distancing may be influential as a signal to individuals about the seriousness of COVID-19 as a public health threat ( Norton et al, 2021 ). To best leverage injunctive norms to promote physical distancing adherence, messaging and conversations promoting physical distancing may be most influential if they are received from a person an individual perceives as sharing a common identity or being a member of the same in-group as them ( Abrams et al, 1990 ; Centola, 2011 ; Van Bavel et al, 2020 ); thus, messages from peers and leaders of groups that individuals identify with (e.g., political and religious leaders) may be most influential.…”
Section: Discussionmentioning
confidence: 74%
“…We consider that this decrease can be explained as follows. Regarding physical activity, although physical activity could be maintained by replacing it with exercise alone or with the family or by hobbies, social distancing was emphasized by the mass media as a social norm 23 , and concern about infecting others increased 15 . This lead to behaviors to avoid social participation.…”
Section: Discussionmentioning
confidence: 99%